Enhancing Rural Children’s English Skills through “Mini English Camp: My English Life!”: An Observational Evaluation - Adaninggar Septi Subekti; Kenny Jessica Aurora Clara Devta; Amelia Putri Aftiana; Andika Rizky Pratama; Immanuel Usodo; Anastasia Graciella Angelina; Rian Raihan Octavian (Indonesian Scientific Journal, 2026)
This article reports on an English language programme named “Mini English Camp: My English Life!” The programme aimed at enhancing the English skills of young learners in the village of Kalijoho, Argosari, Bantul, Yogyakarta. This goal of the programme was continually monitored through observations. The programme, which was part of a month-long service-learning project, was designed and delivered by six students from Universitas Kristen Duta Wacana, with one serving as the lead facilitator. The primary goal of the programme was to introduce basic English language skills in an engaging and accessible way, while also boosting the learners' confidence and interest in English. The participants, aged 6 to 8, had minimal exposure to English in their daily lives, making this initiative crucial for fostering curiosity about the language. Each session, lasting 60 minutes, focused on interactive activities such as songs, games, and practical exercises, aimed at building vocabulary, simple phrases, and communication skills. The programme spanned five meetings, held after school hours to accommodate the children's schedules. The results suggest that, despite the limited number of sessions, the programme successfully introduced young learners to English in a fun and participatory environment.